Portugal aktie 28 januari 1975. Van links naar rechts: André Kloos, Mario Soares, Piet Dankert - Hasselt, A.R. van (1975)
Portugal aktie 28 januari 1975. Van links naar rechts: André Kloos, Mario Soares, Piet Dankert.